Study on seismic behavior of oblique CFRP corrugated plate-steel plate light weight sandwich composite shear wall. (February 2023) - Yu, Jin-Guang; Zhu, Shi-Qi
Abstract: To improve the seismic behavior of the thin steel plate shear wall (SPSW), carbon fiber reinforced polymer (CFRP) is introduced into the thin SPSW, and polyethylene terephthalate (PET) foam is filled between CFRP corrugated plates and steel plate. An oblique CFRP corrugated plate-steel plate lightweight sandwich composite shear wall specimen (hereinafter: sandwich composite plate specimen) is designed. Furthermore, this paper compares the failure mechanism and hysteresis performance of the sandwich composite plate specimen and traditional non-stiffened SPSW specimen under the quasi-static test, and explores the influence of sandwich composite plate on the performance of wallboard. Finally, a simplified finite element model is established and its accuracy is verified by experiments. The results show that compared with the non-stiffened SPSW structure, the initial stiffness of the sandwich composite plate structure is increased by 34.0%, the energy dissipation capacity is increased by 38.44% when loads to 2% drift, and the maximum out-of-plane deformation is reduced by 93.24%. The sandwich composite plate structure shows obvious four-stage stress characteristics, and has good cooperative working performance before the CFRP corrugated plates debond in a large area, also plays a great role in anti-buckling.